2012
DOI: 10.7314/apjcp.2012.13.5.1809
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid Receptors in Gastric Cancer: Expression and Influence on Prognosis

Abstract: Retinoic acid has been recognised as a pivotal compound in cell differentiation, proliferation and malignant transformation (Shyu et al., 1995;Tanaka and De Luca, 2009). Retinoids are natural and synthetic derivatives of retinol (vitamin A). The naturally occuring retinoids, all-trans retinoic acid, 9-cis retinoic acid and 13-cis retinoic acid, are generated from diet-derived retinol. Retinoids are ligands of cellular receptors of retinoic acid, including retinoic acid receptors (RARs) and retinoid X receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 63 publications
(63 reference statements)
1
20
0
1
Order By: Relevance
“…body surface area per day) compared with the dose used in APL treatment and advanced gastric cancer (45 mg/m 2 body surface area per day). 28,50 Remission rates reported in the present study suggest that the addition of ATRA to conventional omeprazole and sucralfate therapy for gastritis can improve the prognosis of gastric dysplasia. In addition, ATRA treatment increased Rb expression and decreased HER2 expression in gastric mucosa.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…body surface area per day) compared with the dose used in APL treatment and advanced gastric cancer (45 mg/m 2 body surface area per day). 28,50 Remission rates reported in the present study suggest that the addition of ATRA to conventional omeprazole and sucralfate therapy for gastritis can improve the prognosis of gastric dysplasia. In addition, ATRA treatment increased Rb expression and decreased HER2 expression in gastric mucosa.…”
Section: Discussionmentioning
confidence: 85%
“…11,12,15,[19][20][21] In human clinical trials, patients with gastric cancer treated with ATRA had a longer survival time compared with control patients. 28 It has been reported that ATRA induced cell-cycle arrest and apoptosis in a gastric carcinoma cell line. 47 It has been suggested that the effect of ATRA on gastric precancerous lesions in rats might be via suppression of proliferating cell nuclear antigen and Bcl-2 protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El receptor se localiza en el citoplasma (isoformas β4) o en el núcleo (β1 y β2) y se une al ácido retinoico (forma activa de la vitamina A), e interviene en la morfogénesis del embrión y en el crecimiento y diferenciación celular (Hu et al 2012), regulando la transcripción de genes específicos. La forma de acción de los receptores se da cuando forman heterodímeros RAR-RXR que se unen a secuencias específicas del ADN (sitios conocidos como DR1-DR5) y actúan como factores de transcripción dependientes de ligando (Hu et al 2012, Altucci y Gronemeyer 2001. El gen RARB es un GST y se especula que se encuentra inactivo en la carcinogénesis gástrica (Mauro et al 2008, Wu et al 2002.…”
Section: Gen Rar-b (Retinoic Acid Receptor Beta)unclassified
“…Subsequently, a series of studies of ATRA on APL and solid tumors were developed at full blast. Vast researches indicated that ATRA could induce cell differentiation and inhibit invasion and migration of multiple solid tumor cells, including breast cancer, gastric carcinoma and colon cancer, and so on (Bengtsson et al, 2013;Hu et al, 2012a;2014bWang et al, 2013aZhang et al, 2013b;2014a;Garattini et al, 2014;Tang et al, 2014). But its application was largely limited because of its poor solubility and high toxicity (Gui et al, 2011;Dhar et al, 2012;Clemens et al, 2013;Wang et al, 2013a;2013b).…”
Section: Introductionmentioning
confidence: 99%